P‐Doping Poly(3‐hexylthiophene) in Solvent Mixtures. Issue 19 (2nd September 2018) - Freeman, Lucas; Miller, Paul; Sapolsky, Marni; Boucher, David
Abstract: One method to improve the conductivity of conjugated polymers, like poly(3‐hexylthiophene) (P3HT), is to "chemically dope" them analogous to inorganic materials. One electron acceptor that has been used in tandem to p‐doped P3HT is 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane (F4TCNQ), and recently there has been much interest in the nature of the interactions between F4TCNQ and P3HT in the solution phase. To date, however, there are few reports that investigate the behavior of F4TCNQ‐doped P3HT in binary solvent mixtures. The study reported herein is an investigation of F4TCNQ‐doped P3HT in mixtures of chloroform (CF) with dichloromethane (DCM) or acetonitrile (AcN), wherein variations in the doping efficiency in these mixtures are observed using UV–vis absorption, Raman, and electron paramagnetic resonance spectroscopic techniques. The contrasting solubility and charge transfer behavior of F4TCNQ‐doped P3HT in CF:DCM and CF:AcN show that judicious selection of solvent mixtures may be exploited to improve the doping efficiency and solution processability of p‐doped P3HT dispersions. Abstract : Absorption, Raman, and X‐band electron paramagnetic resonance spectroscopic techniques are used to investigate charge transfer interactions between 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane and poly(3‐hexylthiophene) in the solution phase and the dependence of these interactions on the chemical characteristics of solvent mixtures.